2020
DOI: 10.1002/1878-0261.12740
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 clustering with engineered tetravalent antibody improves the efficiency and modifies the mechanism of receptor internalization

Abstract: Fibroblast growth factor receptor 1 (FGFR1) transmits signals through the plasma membrane regulating essential cellular processes like division, motility, metabolism, and death. Overexpression of FGFR1 is observed in numerous tumors and thus constitutes an attractive molecular target for selective cancer treatment. Targeted anti‐cancer therapies aim for the precise delivery of drugs into cancer cells, sparing the healthy ones and thus limiting unwanted side effects. One of the key steps in targeted drug delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…Regulation of RTK distribution in the plasma membrane is one of strategies for fine-tuning RTK-dependent signaling [10]. We have previously reported that by using engineered oligomeric FGFR1 ligands it is possible to control activity, endocytosis and cellular level of the receptor [21,22]. Importantly, the architecture of the oligomeric ligands (binding site on the receptor, affinity, oligomeric state, oligomerization scaffold used) played an important role in determining the outcome of FGFR1 modulation [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulation of RTK distribution in the plasma membrane is one of strategies for fine-tuning RTK-dependent signaling [10]. We have previously reported that by using engineered oligomeric FGFR1 ligands it is possible to control activity, endocytosis and cellular level of the receptor [21,22]. Importantly, the architecture of the oligomeric ligands (binding site on the receptor, affinity, oligomeric state, oligomerization scaffold used) played an important role in determining the outcome of FGFR1 modulation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that by using engineered oligomeric FGFR1 ligands it is possible to control activity, endocytosis and cellular level of the receptor [21,22]. Importantly, the architecture of the oligomeric ligands (binding site on the receptor, affinity, oligomeric state, oligomerization scaffold used) played an important role in determining the outcome of FGFR1 modulation [21,22]. Therefore, we have sought to develop novel strategies to generate multivalent FGFR1 ligands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated level of FGFR1 has been observed in various tumor types, like breast, lung, head or neck cancers [ 16 21 ]. Thus, FGFR1 is considered as an attractive tumor biomarker and several approaches for selective treatment of FGFR1 overproducing cancer cells have been developed, including cytotoxic conjugates with antibody fragments or natural ligands as targeting agents [ 22 – 25 ]. We have recently shown that the spatial distribution of FGFR1 at the plasma membrane determines efficiency and mechanism of receptor endocytosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%